2007
DOI: 10.1161/circulationaha.106.635011
|View full text |Cite
|
Sign up to set email alerts
|

Defining Obesity Cut Points in a Multiethnic Population

Abstract: , MBBS, DPhil, FRCP(c); for the SHARE Investigators Background-Body mass index (BMI) is widely used to assess risk for cardiovascular disease and type 2 diabetes. Cut points for the classification of obesity (BMI Ͼ30 kg/m 2 ) have been developed and validated among people of European descent. It is unknown whether these cut points are appropriate for non-European populations. We assessed the metabolic risk associated with BMI among South Asians, Chinese, Aboriginals, and Europeans. Methods and Results-We rando… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

27
374
4
4

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 480 publications
(409 citation statements)
references
References 33 publications
27
374
4
4
Order By: Relevance
“…More recent immigrants were also less likely to be overweight/obese than more settled South Asians (OR = 0.59 for 5 to \10 years; 95 % CI 0.35, 0.98). Results were unchanged in sensitivity analyses with different cut-points for BMI [60][61][62][63][64]. We found that South Asian immigrants who were overweight/obese had 2.32 greater odds (95 % CI 1.11, 4.86) of reporting diabetes and 2.19 greater odds (95 % CI 1.34, 3.56) of reporting hypertension than those with a healthy BMI.…”
Section: Resultsmentioning
confidence: 87%
“…More recent immigrants were also less likely to be overweight/obese than more settled South Asians (OR = 0.59 for 5 to \10 years; 95 % CI 0.35, 0.98). Results were unchanged in sensitivity analyses with different cut-points for BMI [60][61][62][63][64]. We found that South Asian immigrants who were overweight/obese had 2.32 greater odds (95 % CI 1.11, 4.86) of reporting diabetes and 2.19 greater odds (95 % CI 1.34, 3.56) of reporting hypertension than those with a healthy BMI.…”
Section: Resultsmentioning
confidence: 87%
“…Our proposed BMI cut-offs are congruent with the previously recommended BMI cut-offs for SA by Misra et al (8) , who performed ROC curve analysis and suggested 23·0 kg/m 2 for females and 24·0 kg/m 2 for males. Ramachandran et al (4) studied South Indians of both sexes who attended hospitals in India found a MetS prevalence of 42 % overall, 36 % for men and 47 % for women (4,41) . In 2011, Dodani et al (33) conducted a community-based cross-sectional study to ascertain the prevalence of MetS in South Asian immigrants to examine the association between MetS and HDLC function, apolipoprotein (APO1) gene polymorphisms and subclinical coronary artery disease using common carotid intima-media thickness as a surrogate marker.…”
Section: Discussionmentioning
confidence: 99%
“…This means that as the mean values increase with the corresponding higher distributions, it would result automatically in a higher cut point using the ROC method. 37 Therefore, the higher cut point of BMI in women and similar cut points of WC in both genders could be attributed to the high prevalence of general and central obesity in Iranian women. 38 Recently, in a national survey of Iranian adults, the age-adjusted means of WCs among men and women were 86.6 and 89.6 cm, respectively.…”
Section: Obesity Variables To Predict Cardiovascular Events F Hadaeghmentioning
confidence: 95%